Hydrothermal synthesis of tobermorite from diatomite and its adsorption performance for methylene blue. (May 2015) - Zhang, Y.; Jing, Z.; Li, Y.; Fan, J.; Kan, W.
Abstract : Disposal of dyes wastewater effluents is one of the most important factors in many industries. Methylene blue is the most commonly used dyes in industries and is very difficult to degrade due to its complex structures. Diatomite is one of the excellent adsorbents owing to its unique properties. However, the small powder form of diatomite, which leads to a large amount sludge produced easily, has limited its wide application in environmental engineering. In our study, diatomite was solidified hydrothermally at low temperature (≤ 200°C) on the basis of sustaining the inherent properties of diatomite. The results showed that tobermorite was found to exert a positive effect on its strength and porosity, and also had higher methylene blue adsorption capability compared with diatomite. The thermodynamic parameters indicated that the adsorption of methylene blue with tobermorite formation was an endothermic and spontaneous process.